Reversion of developmental mode in insects: evolution from long germband to short germband in the polyembrionic wasp Macrocentrus cingulum Brischke. Issue 4 (30th June 2014) - Sucena, Élio; Vanderberghe, Koen; Zhurov, Vladimir; Grbić, Miodrag
SUMMARY Germband size in insects has played a central role in our understanding of insect patterning mechanisms and their evolution. The polarity of evolutionary change in insect patterning has been viewed so far as the unidirectional shift from the ancestral short germband patterning of basal hemimetabolous insects to the long germband patterning observed in most modern Holometabola. However, some orders of holometabolic insects display both short and long germband development, though the absence of a clear phylogenetic context does not permit definite conclusions on the polarity of change. Derived hymenoptera, that is, bees and wasps, represent a classical textbook example of long germband development. Yet, in some wasps putative short germband development has been described correlating with lifestyle changes, namely with evolution of endoparasitism and polyembryony. To address the potential reversion from long to short germband, we focused on the family Braconidae, which displays ancestral long germband development, and examined the derived polyembryonic braconid Macrocentrus cingulum. Using SEM analysis of M. cingulum embryogenesis coupled with analyses of embryonic patterning markers, we show that this wasp evolved short germband embryogenesis secondarily, in a way that is reminiscent of embryogenesis in the beetle Tribolium castaneum. This work shows that the evolution of germband size in insects is a reversible process that may correlate with other life‐history traits and suggests broader implications on the mechanisms and evolvability of insect development.